1

I need to split this equation in two pages. Can you help me? Thanks

\documentclass[11 pt,a4paper,oneside,openany, notitlepage]{article}
\input epsf
\usepackage{amsmath, amssymb, graphics}
\newcommand{\mathsym}[1]{{}}
\usepackage{amsthm}
\usepackage{amsfonts}
\marginparwidth 0pt
\oddsidemargin 0pt
\evensidemargin 0pt
\marginparsep 0pt
\linespread{1.5}
\topmargin 0pt
\textwidth 6.5in
\textheight 8.5 in

\begin{document}
\begin{equation}
\begin{aligned}
\Theta^\diamond_o:=\{\theta & \in \Theta | \\
&
\begin{pmatrix}
H_l^{(1)}(x;\theta) \mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x) \leq H_u^{(1)}(x;\theta)\mathbb{P}(X=x) \\
H_l^{(2)}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x) \leq H_u^{(2)}(x;\theta) \mathbb{P}(X=x)\\
\vdots\\
H_l^{(h)}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x) \leq H_u^{(h)}(x;\theta)\mathbb{P}(X=x) \\
\vdots\\
H_l^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x) \leq H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \\
\end{pmatrix}\\
&\forall x \in \mathcal{X}\}=\{\theta \in \Theta | \\
&
\begin{pmatrix}
H_l^{(1)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)-H_u^{(1)}(x,n;\theta)\mathbb{P}(X=x) \leq 0\\
H_l^{(2)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)-H_u^{(2)}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\vdots\\
H_l^{(h)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)-H_u^{(h)}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\vdots\\
H_l^{(2^{n-1})}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)-H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\end{pmatrix}\\
&\forall x \in \mathcal{X}\}\subseteq\{\theta \in \Theta | \\
&
\begin{pmatrix}
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(1)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)\right)\mathbb{P}(X=x) \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)-H_u^{(1)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(2)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)-H_u^{(2)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\vdots\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(h)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)-H_u^{(h)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\vdots\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(2^{n-1})}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)-H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0
\end{pmatrix}\\
&\}=\{\theta \in \Theta | \\
&
\begin{pmatrix}
\mathbb{E}_X\left(H_l^{(1)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X)\right) \leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X)-H_u^{(1)}(X;\theta)\mathbb{P}(X)\right)\leq 0\\
\mathbb{E}_X\left(H_l^{(2)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X)\right)\leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X)-H_u^{(2)}(X;\theta)\mathbb{P}(X)\right)\leq 0\\
\vdots\\
\mathbb{E}_X\left(H_l^{(h)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X)\right)\leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X)-H_u^{(h)}(X;\theta)\mathbb{P}(X)\right) \leq 0\\
\vdots\\
\mathbb{E}_X\left(H_l^{(2^{n-1})}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X)\right) \leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X)-H_u^{(2^{n-1})}(X;\theta)\mathbb{P}(X)\right) \leq 0
\end{pmatrix}\\
&\forall n \in \mathbb{N}\}
\end{aligned}
\end{equation}
\end{document}
  • \allowdisplaybreaks Also don't input epsf :-) – David Carlisle Apr 8 '14 at 16:11
0

If you stick with the default article class, you may need 3 pages, but I squeeze it onto 2 pages, just for demonstration.

\documentclass[11 pt,a4paper,oneside,openany, notitlepage]{article}
\input epsf
\usepackage{amsmath, amssymb, graphics}
\newcommand{\mathsym}[1]{{}}
\usepackage{amsthm}
\usepackage{amsfonts}
\marginparwidth 0pt
\oddsidemargin 0pt
\evensidemargin 0pt
\marginparsep 0pt
\linespread{1.5}
\topmargin 0pt
\textwidth 6.5in
\textheight 8.5 in

\begin{document}
\begin{align*}
\Theta^\diamond_o:=\{\theta & \in \Theta | \\
&
\begin{pmatrix}
H_l^{(1)}(x;\theta) \mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x) \leq H_u^{(1)}(x;\theta)\mathbb{P}(X=x) \\
H_l^{(2)}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x) \leq H_u^{(2)}(x;\theta) \mathbb{P}(X=x)\\
\vdots\\
H_l^{(h)}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x) \leq H_u^{(h)}(x;\theta)\mathbb{P}(X=x) \\
\vdots\\
H_l^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x) \leq H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \\
\end{pmatrix}\\
&\forall x \in \mathcal{X}\}=\{\theta \in \Theta | \\
&
\begin{pmatrix}
H_l^{(1)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)-H_u^{(1)}(x,n;\theta)\mathbb{P}(X=x) \leq 0\\
H_l^{(2)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)-H_u^{(2)}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\vdots\\
H_l^{(h)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)-H_u^{(h)}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\vdots\\
H_l^{(2^{n-1})}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)-H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\end{pmatrix}\\
&\forall x \in \mathcal{X}\}\subseteq\{\theta \in \Theta | \\
&
\begin{pmatrix}
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(1)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)\right)\mathbb{P}(X=x) \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)-H_u^{(1)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(2)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)-H_u^{(2)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\vdots\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(h)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)-H_u^{(h)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\vdots\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(2^{n-1})}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)-H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0
\end{pmatrix}\\
&\}=\{\theta \in \Theta |\\
&\hspace{5.12in}\llap{\text{(continued on next page)}}
\end{align*}
\clearpage
\begin{equation}
\begin{aligned}
\phantom{\Theta^\diamond_o:=\{\theta} & 
  \hspace{5.12in}\llap{\text{(continued from previous page)}}\\
&
\begin{pmatrix}
\mathbb{E}_X\left(H_l^{(1)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X)\right) \leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X)-H_u^{(1)}(X;\theta)\mathbb{P}(X)\right)\leq 0\\
\mathbb{E}_X\left(H_l^{(2)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X)\right)\leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X)-H_u^{(2)}(X;\theta)\mathbb{P}(X)\right)\leq 0\\
\vdots\\
\mathbb{E}_X\left(H_l^{(h)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X)\right)\leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X)-H_u^{(h)}(X;\theta)\mathbb{P}(X)\right) \leq 0\\
\vdots\\
\mathbb{E}_X\left(H_l^{(2^{n-1})}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X)\right) \leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X)-H_u^{(2^{n-1})}(X;\theta)\mathbb{P}(X)\right) \leq 0
\end{pmatrix}\\
&\forall n \in \mathbb{N}\}
\end{aligned}
\end{equation}
\end{document}

enter image description here

enter image description here

1

If really need to this then you should use a simple align* environment rather than aligned inside equation, and issue \allowdisplaybreaks first, preferably contained in a group.

\documentclass[11 pt,a4paper,oneside,openany, notitlepage]{article}
\usepackage{mathtools, amssymb, graphics}
\newcommand{\mathsym}[1]{{}}
\usepackage{amsthm}
\usepackage{amsfonts}
\marginparwidth 0pt
\oddsidemargin 0pt
\evensidemargin 0pt
\marginparsep 0pt
\linespread{1.5}
\topmargin 0pt
\textwidth 6.5in
\textheight 8.5 in

\DeclarePairedDelimiterX{\Set}[2]{\{}{\}}{\, #1 \,\delimsize\vert\, #2 \,}

\begin{document}
{\allowdisplaybreaks
\begin{align*}
\Theta^\diamond_o&:=\Set*{\theta  \in \Theta}{
H_l^{(h)}(x;\theta)\mathbb{P}(X=x) \leq \mathbb{P}(G_{\cdot
j}=g_{\bullet}^{(h)},X=x) \leq H_u^{(h)}(x;\theta)\mathbb{P}(X=x)\ h=1,\dots,2^{n-1},\
\forall x \in \mathcal{X}}\\&=\Set*{\theta \in \Theta}{
\begin{pmatrix}
H_l^{(1)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)-H_u^{(1)}(x,n;\theta)\mathbb{P}(X=x) \leq 0\\
H_l^{(2)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)-H_u^{(2)}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\vdots\\
H_l^{(h)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)-H_u^{(h)}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\vdots\\
H_l^{(2^{n-1})}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x) \leq 0\\ \mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)-H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x) \leq 0\\
\end{pmatrix}
\forall x \in \mathcal{X}}\\&\subseteq\Set*{\theta \in \Theta}{
\begin{pmatrix}
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(1)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)\right)\mathbb{P}(X=x) \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X=x)-H_u^{(1)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(2)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X=x)-H_u^{(2)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\vdots\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(h)}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X=x)-H_u^{(h)}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0\\
\vdots\\
\sum_{x \in \mathcal{X}}^{}\left(H_l^{(2^{n-1})}(x;\theta) \mathbb{P}(X=x)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)\right)\mathbb{P}(X=x)  \leq 0\\ 
\sum_{x \in \mathcal{X}}^{}\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X=x)-H_u^{(2^{n-1})}(x;\theta)\mathbb{P}(X=x)\right)\mathbb{P}(X=x)  \leq 0
\end{pmatrix}
}\\&=\Set*{\theta \in \Theta}{
\begin{pmatrix}
\mathbb{E}_X\left(H_l^{(1)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X)\right) \leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(1)},X)-H_u^{(1)}(X;\theta)\mathbb{P}(X)\right)\leq 0\\
\mathbb{E}_X\left(H_l^{(2)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X)\right)\leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2)},X)-H_u^{(2)}(X;\theta)\mathbb{P}(X)\right)\leq 0\\
\vdots\\
\mathbb{E}_X\left(H_l^{(h)}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X)\right)\leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(h)},X)-H_u^{(h)}(X;\theta)\mathbb{P}(X)\right) \leq 0\\
\vdots\\
\mathbb{E}_X\left(H_l^{(2^{n-1})}(X;\theta) \mathbb{P}(X)-\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X)\right) \leq 0\\ 
\mathbb{E}_X\left(\mathbb{P}(G_{\cdot j}=g_{\bullet}^{(2^{n-1})},X)-H_u^{(2^{n-1})}(X;\theta)\mathbb{P}(X)\right) \leq 0
\end{pmatrix}
\forall n \in \mathbb{N}}
\end{align*}}

\end{document}

However, your side conditions contain many repeated patterns, and could be replaced by expressions such as

 H_^{(h)}.... for h=1,\dots,2^{n-1}...

obviating the need for such a large display.

  • Thank you, but I can't download the package mathtools. – user49271 Apr 8 '14 at 16:26
  • mathtools is part of standard tex distributions, and available at ctan.org/pkg/mathtools – Andrew Swann Apr 9 '14 at 10:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.